2013
DOI: 10.1590/s0001-37652013005000039
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and hematological studies of Trypanosoma spp. infecting ornamental armored catfish from Guamá River-PA, Brazil

Abstract: A total of 281 specimens of freshwater armored ornamental fish species (Leporacanthicus galaxias, Lasiancistrus saetiger, Cochliodon sp., Hypostomus sp., Pseudacanthicus spinosus, Ancistrus sp. and Rineloricaria cf. lanceolata) were captured at the hydrological basin of Guamá River, Pará, Brazil. The infection by Trypanosoma spp. was inspected. The morphological and morphometric characterization of the parasites and the hematological parameters were determined. Leporacanthicus galaxias and Pseudacanthicus spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
2
17
1
3
Order By: Relevance
“…The RBC count, hematocrit and MCV of Hypostomus spp. in this study were similar to those reported by Fujimoto et al (2013) for the same host infected by Trypanosoma spp., while the hemoglobin concentration, MCHC and MCH levels were lower. The hemoglobin concentration and RBC number showed an increase with the intensity of Trypanosoma spp.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The RBC count, hematocrit and MCV of Hypostomus spp. in this study were similar to those reported by Fujimoto et al (2013) for the same host infected by Trypanosoma spp., while the hemoglobin concentration, MCHC and MCH levels were lower. The hemoglobin concentration and RBC number showed an increase with the intensity of Trypanosoma spp.…”
Section: Discussionsupporting
confidence: 92%
“…It seems that the virulence factor that leads to anemia is a protease. However, Fujimoto et al (2013) reported that the RBC parameters of Hypostomus sp., Ancistrus sp. and Rineloricaria lanceolata were not influenced by infection by Trypanosoma sp., but the RBC and hematocrit level in Lasiancistrus saetiger increased while hemoglobin concentration decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3A) e o VCM (Fig. 3B) (Silva et al, 2012;Fujimoto et al, 2013). CHCM: concentração de hemoglobina corpuscular média.…”
Section: Resultsunclassified
“…As amostras de sangue foram usadas para determinação dos níveis de glicose plasmática, utilizando-se medidor automático (Prestige IQ 50), hematócrito, pelo método de microhematócrito (Goldenfarb et al, 1971), concentração da hemoglobina, pelo método da cianometa-hemoglobina e contagem de eritrócitos totais em câmara de Neubauer. De posse dos dados de eritrócitos, hematócrito e hemoglobina, foram calculados os índices hematimétricos de Witronbe: volume corpuscular médio (VCM), hemoglobina corpuscular média (HCM) e concentração de hemoglobina corpuscular média (CHCM).…”
Section: Methodsunclassified